Internal medicine clerkship guide : - Paauw, S. Douglas (Mosby, 2003)
This practical, pocket-sized reference provides guidance on the core clinical information essential for rotating through an internal medical clerkship. Divided into three sections, the text outlines the practical skills and procedures needed on rotation, organizes clinical discussions by presentations (symptom, sign, or abnormal lab value), and presents discussions of problems organized by specific diagnosis.